MEMBANGUN DESAIN HUBUNGAN INDUSTRIAL DALAM MENCAPAI KEHARMONISAN ANTAR PEGAWAI DENGAN MAJEMEN DI HOTEL ZODIAK SUTAMI - Ririn Rustini; Neng Santy; Ica Mawarni; Resya Dwi Marselina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Abstrak. In this day and age, competition for business companies is increasingly fierce, many find problems that can cause the company to fail or compete. From this competition, it is necessary that the company will be able to achieve the goals it has set if it can have employees who have good performance at work, this can really help the company to develop even better. Therefore, the formulation in this research is about the impact of workload on employee performance at the Zodiak Sutami hotel and also what kind of work agreement is used. The method used in this research is qualitative so that it can analyze industrial relations between employees at the Zodiak Sutami hotel. The results of this research are that the form of work agreement at the Zodiak Sutami Hotel is a Specific Time Work Agreement (PKWT) with a period of 24 months. Overtime pay is permitted, and companies are required to provide overtime pay in accordance with statutory regulations. The industrial relations that occur at the hotel also seem harmonious and the leaders at the Zodiak Sutami hotel try to be a place for their employees to tell their stories. Keywords: Performance, Employees, Work, Management, Organization.